Osteomyelitis in traumatic exposed bone following flap coverage - Jie, Woo Qi (2018)
Introduction: Flap coverage of traumatic exposed bone is important to prevent osteomyelitis and promote bone healing. These surgeries were previously studied, comparing time of bone coverage from trauma, and different components of flaps used; outcomes studied were flap survival, infection, osteomyelitis and duration of bone healing. Previous studies did not focus on osteomyelitis alone after bone coverage. Objectives: Our study was designed to review the factors associated with osteomyelitis after bone coverage Methods: This was a single-centre retrospective observational study conducted in Hospital Universiti Sains Malaysia. Case records of 88 patients who underwent traumatic bone coverage with flaps between 1998 till 2006 were reviewed. Osteomyelitis as a complication, length of exposed bone, exposed fracture site, time from trauma to bone coverage, and infection at flap site post coverage were studied. Results: We performed 56 free flaps and 32 local flaps to cover the traumatic exposed bones; 46 were muscle flaps, 31 were fascia flaps and 11 were osseofasciocutaneous flaps. Most flap coverages were done in between 72 hours and 90 days. Mean of exposed bone length in osteomyelitis group was 4.5cm (range=1-32cm), and nonosteomyelitis group was 6.86cm (range=1-15cm). Incidence of osteomyelitis after bone coverage with flaps was 39.8%. There were significant statistical correlations between time from trauma to bone coverage (OR=1.027, 95%CI=1.005-1.051, p=0.017), and infection at flap site post coverage (OR=0.023, 95%CI=0.005-0.102, p=<0.001) with osteomyelitis after coverage. Flap coverages done after 28.5 days were associated with higher incidences of osteomyelitis. Incidentally, diabetes mellitus (OR=2.321, 95%CI=0.728-7.400, p=0.155) was found to be associated with osteomyelitis after flap coverage. There were no statistically significant correlations between length of exposed bone and exposed fracture site with osteomyelitis after coverage. Conclusions: Osteomyelitis after flap coverage of exposed bone is not an uncommon problem. Risk factors include delay in performing flap coverage, infection at flap site after coverage and diabetes mellitus. Bone coverage with flap need to be performed as soon as patients’ general and local wound conditions permits, to prevent infections and osteomyelitis.